محددات خلق القيمة على مستوى المؤسسات المالية العاملة في الأردن دراسة حالة البنك العربي - خلال الفترة 2015 - 2020: Determinants of value creation in financial institutions operating in Jordan - a case study of Arab Bank during the period 2015-2020 - فيلالي طارق (Journal of North African Economies, 2025)
This study aimed to investigate the determinants of the value creation process at the level of financial institutions operating in Jordan during the period 2015-2020. In order to achieve the objectives of the study, the researcher subjected the financial statements of the Arab Bank to a financial analysis process in order to calculate a set of financial indicators represented in the indicators of financial balance in addition to the profitability ratios of the bank, then each of the market value-added and economic value-added indicators will be calculated. The study concluded that the indicators for the profitability measurement, represented by the ROA, ROE and ROIC, can be considered as the main determinants of the process of creating value in our targeted company. The study concluded also that the level of market value added of the bank does not reach the levels of added value achieved by financial institutions operating in advanced financial markets.